2021
DOI: 10.1002/ceat.202100068
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Hydrodynamics and Filtration in a Membrane‐Assisted Stirred Slurry Reactor

Abstract: A membrane‐assisted stirred slurry reactor is developed by equipping a membrane tube into a stirred tank. Liquid‐solid flow is simulated by the Euler‐Lagrange method with filtration and particle deposition models. Acceptable predictions on the cake mass and particle deposition patterns are achieved by comparing with experimental data. The introduction of the membrane tube generates an asymmetric flow field. Shear stress on the membrane surface has a direct influence on the particle deposition. Increasing the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The study by Chen et al showed that the enhanced rotary tangential flow was beneficial in the shedding of deposited particles and the reduction of cake resistance. In addition, the studies of semicontinuous membrane reactors showed that the stirring rate had a nonlinear relationship with the membrane filtration performance, and the stirring rate was mostly set at 0 rpm in the membrane separation process. , Later, Qiu et al used the multiphase particle-in-cell method combined with the force equations of particles to calculate the deposition rate and found that increasing the shear rate on the membrane surface could effectively reduce particle deposition, while the axial flow along the membrane bundle cannot control membrane fouling. However, the filtration did not reach the quasi-steady state.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Chen et al showed that the enhanced rotary tangential flow was beneficial in the shedding of deposited particles and the reduction of cake resistance. In addition, the studies of semicontinuous membrane reactors showed that the stirring rate had a nonlinear relationship with the membrane filtration performance, and the stirring rate was mostly set at 0 rpm in the membrane separation process. , Later, Qiu et al used the multiphase particle-in-cell method combined with the force equations of particles to calculate the deposition rate and found that increasing the shear rate on the membrane surface could effectively reduce particle deposition, while the axial flow along the membrane bundle cannot control membrane fouling. However, the filtration did not reach the quasi-steady state.…”
Section: Introductionmentioning
confidence: 99%
“…The closer the membrane tube was to the junction of the forced vortex and the free vortex, the higher the membrane flux was. Experiments and simulations by Qiu et al 12 had shown that using straight-blade impellers, increasing the impeller velocity, and moving the membrane tube close to the impeller could increase the shear stress and reduce membrane fouling. It is generally accepted that increasing the shear stress enhances the turbulence and instability of the fluid, thereby promoting the migration of particles on the membrane surface, which can effectively reduce membrane fouling.…”
Section: Introductionmentioning
confidence: 99%